The DEAD-box RNA helicase 27 negatively regulates the replication of porcine reproductive and respiratory syndrome virus by mediating GP2a autophagy degradation and inducing interferon-β production - Chen, Binghua; Luo, Yunyan; Chen, Yongjie; Wang, Jingxing; Yan, Jiecong; He, Zhan; Li, Fangfang; Guo, Chunhe (Frontiers in Immunology, 2025)
Porcine reproductive and respiratory syndrome virus (PRRSV) causes severe economic losses to the swine industry, with its replication and immune evasion mechanisms remaining incompletely understood. While DEAD-box helicases (DDXs) are known to either promote or inhibit viral infections, no prior studies have explored the role of DDX27 in viral pathogenesis. Here, we investigated the role of DDX27 in PRRSV infection. PRRSV infection induced the upregulation of endogenous DDX27 mRNA without affecting protein levels in Marc-145 cells. Functional studies revealed that overexpression of DDX27 significantly inhibited PRRSV N protein and mRNA accumulations, while silencing DDX27 enhanced viral replication. Using yeast two-hybrid and co-immunoprecipitation assays, we identified a specific interaction between DDX27 and the viral structural protein GP2a, but not with GP3, M, or non-structural proteins. Mechanistically, DDX27 promoted GP2a degradation via mediating selective autophagy pathway and activated IFN-β production, thereby suppressing PRRSV replication and enhancing host immune responses. These findings reveal DDX27 as a novel antiviral factor that targets PRRSV through dual mechanisms. This study broadens our understanding of the DDX family’s role in PRRSV infection and highlights DDX27 as a potential therapeutic target for controlling PRRSV.